Warming accelerated phosphorus release from the sediment of Lake Chaohu during the decomposition of algal residues: A simulative study - Jiayu Hu; Qiong Zhao; Ping Zeng; Qiang Tang; Qingye Sun; Hongbin Yin (PLoS ONE, 2025)
Algal decomposition plays an important role in affecting phosphorus (P) release from sediments in eutrophic lakes under global warming. Yet how rising air temperature affect endogenous P release from sediments during the algal decomposition is poorly understood. In this study, effect of increasing air temperature on endogenous P release was investigated. A 22-day laboratory warming simulation experiment was conducted, with the overlying water and sediments collected from Lake Chaohu incubated in microcosms at three temperatures (21, 28 and 37°C). Dynamics of P fractions and related physiochemical properties in water and sediments were measured, and P release rate from sediments was calculated. Rising air temperature significantly reduced redox potential, but elevated pH, dissolved organic carbon (C) and alkaline phosphatase activity in water. For the average value during incubation, rising temperature significantly elevated P release rate and soluble reactive P by 3 times in overlying water, and greatly reduced total organic P (by 19.0%) in sediments, while did not affect total inorganic P in sediments. The NH4Cl-Po and NaHCO3-Po concentrations in sediments showed the greatest decrease (accounting for 97.6% of total decrease) during the experiment. Dynamics of P release rate, soluble reactive P, dissolved organic C in water and organic P, total organic C in sediments during incubation were also differed among different temperatures. The P release rate was significantly and negatively correlated with dissolved organic C and redox potential at all temperatures, negatively correlated with sediment inorganic P at 21°C, while negatively correlated with sediment organic P at 37°C. The results revealed that rising temperature strongly stimulated endogenous P release from sediments during the decay of algal residues, which was mainly due to the acceleration of organic P mineralization Warming-induced changes in the amount and dynamics of dissolved organic C played the dominant role in accelerating P release from sediments.